2019
DOI: 10.1101/gad.327593.119
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for targeting BCL6 inMLL-rearranged acute lymphoblastic leukemia

Abstract: Chromosomal rearrangements of the mixed lineage leukemia (MLL) gene occur in ∼10% of B-cell acute lymphoblastic leukemia (B-ALL) and define a group of patients with dismal outcomes. Immunohistochemical staining of bone marrow biopsies from most of these patients revealed aberrant expression of BCL6, a transcription factor that promotes oncogenic B-cell transformation and drug resistance in B-ALL. Our genetic and ChIP-seq (chromatin immunoprecipitation [ChIP] combined with high-throughput sequencing) analyses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 53 publications
1
30
1
Order By: Relevance
“…Moreover, it was shown that BCL-6 is able to bind the BCL2L11 locus (BIM) and consequently regulates BIM expression. The deletion of BCL-6 induced an increased BIM level [ 49 ]. Altogether, a high BCL-6 expression keeps pro-apoptotic BIM under control, which in turn prevents apoptosis induction in MLL -rearranged B-ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that BCL-6 is able to bind the BCL2L11 locus (BIM) and consequently regulates BIM expression. The deletion of BCL-6 induced an increased BIM level [ 49 ]. Altogether, a high BCL-6 expression keeps pro-apoptotic BIM under control, which in turn prevents apoptosis induction in MLL -rearranged B-ALL.…”
Section: Discussionmentioning
confidence: 99%
“… Methyltransferase activity required for haematopoiesis? HSPC transcriptional response following deletion MLL1 Vav-Cre No change in ST-HSC or LT-HSC numbers at E13.5 in FL [ 79 ] No change in LSK CD48 − numbers by E15.5 in FL [ 82 ] Very low short term and no long term repopulation capacity [ 82 ] No change in LSK CD48 − numbers by E15.5 in FL (Vav-Cre) [ 82 ] 3 weeks [ 82 ] Not quantified Significantly defective myeloid output in CFU [ 79 , 82 ] No, foetal haematopoiesis proceeds normally (Vav-Cre); no change in global H3K4 [ 84 ] In ESC, promotes mesodermal and haematopoietic cell fate [ 113 ] Loss of HoxA cluster in HSPC [ 76 , 78 , 79 , 80 ] HoxB cluster in ESC [ 125 ] MLL2 Germline KO only – No indication for requirement in haematopoiesis [ 88 ] No analysis No analysis No analysis No analysis No analysis No SET mutants No ChiP in null HSPCs No analysis MLL3 Germline KO mice die shortly after birth, no obvious defects [ 94 ] Note - All experimental data from p53 null E13.5.-E14.5 FL HSPCs transplanted into adult mice [ 102 ] shRNA - competitive transplants – increased number of LT-HSC, loss of ST-HSC [ 102 ] No analysis No Vav-Cre mice Reduced MPP, CMP, GMP, no change to MEP [ 102 ] Reduced myeloid CFU output [ 102 ] No SET mutants in blood context Loss of H3K3me3 at some observed loci [ 102 ] Downregulation of early haematopoietic progenitor differentiation, correlation to 7q MDS [ 102 ] MLL4 Germline KO...…”
Section: Mll1 Is Required For Foetal and Adult Bloodmentioning
confidence: 99%
“…Further implicated was a network of various mRNAs and microRNAs, and no single candidate gene could explain the observed phenotype, suggesting that these RNA candidates act between Mll1 and RAS-MEK-ERK signalling. Further insight into Mll1 function during normal B-cell development has been derived from the analysis of MLL-AF4 patient data, where an increased MLL1 and BCL6 expression signature was identified [ 84 ]. Virally induced Cre-mediated deletion of Mll1 in murine pre-B and mature splenic B-cells resulted in a loss of Bcl6 upregulation from 2 weeks.…”
Section: Mll1 Is Required For Foetal and Adult Bloodmentioning
confidence: 99%
See 2 more Smart Citations